Combination of Ginseng and Curcumin Loaded Polymeric Nanoparticles: A Novel Approach to Check Synergistic Effect for the Topical Treatment of Diabetic Retinopathy - Laddha, Umesh; Moravkar, Kailas; Dashputre, Neelam; Gadkari, Yatin; Gaikwad, Sachin; Kshirsagar, Sanjay (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Diabetic Retinopathy (DR) is the worst complication of diabetes which is treated by the invasive methods. The proposed study involves the development of novel combinational therapy for the topical management of diabetic-retinopathy. Materials and Methods: Formulation involves the combination of previously investigated curcumin nanoparticles with newly fabricated ginseng nanoparticles. Both drugs were loaded individually in the PLGA 50:50 polymer. The ginseng-PLGA nanoparticles were optimized by using 32-factorial design to investigate the impact of process parameter (HPH pressure) and polymer (PLGA concentration) by using size of nanoparticle, PDI and % entrapment as the response. Prepared nanoparticles were investigated for various parameters viz. zeta potential, XRD, DSC, SEM, TEM and in vitro drug release. Formulation efficacy was investigated on STZ induced diabetic Wistar Rats. Results: The particle size, PDI, and %EE for ginseng nanoparticles were found to be 167.5-350.8 nm, 0.264-0.699, and 69-95.6%, respectively. The batch F8 (HPH pressure 20 kPsi and PLGA 100 mg) with particle size 168.1 nm, PDI 0.264 and 92.3% entrapment efficiency was selected as the optimized batch and further spray dried. Zeta potential of optimized formulation was found to -21.5 mV. Optimized batch showed 78.58±1.54% cumulative drug release at the end of 10 hr. The XRD, DSC, TEM and SEM analysis confirmed the entrapment of drug in polymeric strand. In the lateral stage, the nanoparticles of curcumin and ginseng were investigated on Wistar rats which showed significant control over the VEGF, TNF-α and IL-6 in comparison to treatment of individual ginseng nano-particles. Conclusion: The obtained results confirmed the impact of combinational therapy over the diabetic retinopathy.
Keywords: Combinational Treatment; Ginseng Nanoparticles; Curcumin Nanoparticles; VEGF; Interleukins; Diabetic Retinopathy; Ophthalmology; Alternative Medicine